Maturação fisiológica e adaptação do teste de envelhecimento acelerado para sementes de fumo - Medeiros, Everton Maksud (2008)
The objective of this first work was to evaluate the efficience of the accelerated aging test to the evaluation of the vigor in tobacco seeds (Nicotiana tabacum L.). Three hybrids of Virginia type seeds were used: CSC 405, K 326 and CSC 459 with two quality levels (high and medium). The seeds were evaluated according to their standard germination and vigor: first counting, traditional accelerated aging, aging with salt saturated solution, and salt non saturated solution in the following condition: (temperature of 38°C and exposition time of 18 hours). (41°C with period of 12, 24, 36, 48, 60 and 72 hours) and (temperature of 45°C with period of 72 hours). It allowed to conclude that: a) the vigor of the portion of the tobacco seeds of hybrids CSC 405, K 326 and CSC 459 can be evaluated through the accelerated aging test with salt saturated solution using temperature of 45 ± 2°C and exposition time of 72 hours; b) the vigor of the portion of the tobacco seeds of hybrids CSC 405 and CSC 459 can be evaluated: - through the traditional accelerated aging test using temperature of 38 ± 2°C and exposition time of 18 hours or temperature of 41 ± 2°C and period of 60 hours; - through accelerated aging test with salt non saturated solution using temperature of 38 ± 2°C and period of 18 hours or temperature of 41 ± 2°C and period of 48 hours; - through accelerated aging test salt saturated solution using temperature of 41± 2°C and period of 48, 60 and 72 hours c) the vigor of tobacco seeds is not evaluated correctly in the first counting of the germination test. The aim of this work was to determine the harvest time of the seeds aiming at the attainment of seeds with a better physiological maturation possible. Seeds of five tobacco hybrids of Virginia Type were used: CSC 416, CSC 439, CSC 444, CSC 458 and CSC 459. The seeds were sowed in a foam tray and conducted in the Float system, producing changes with good quality, achieving the ideal size to the ix transplant, the spacing between lines was 2,0m and 0,5m between plants and there were about 10.000 plants.ha-1. It was 500Kg.ha-1 of NPK in the formulation 10-16-10 of basis fertilization and two saltpetre applications with 200Kg.ha-1 of covering fertilization. According to the planned management it was executed the elimination of the main stem, leaving two to three secondary stems. The plants were pollinated in different days, marking the pollinated flowers. The physiological quality was evaluated by the germination tests and accelerated aging test according to the established methodology in the first work. To determine the coloration of the fruits in the right moment of the crop, they were photographed in all days of the crop in order to obtain a standard of colours, aiming to facilitate further seeds crop. The obtained results allowed to conclude that: a) maturation point of tobacco seeds changes from the twenty-first to twenty-eighth day after anthesis; b) the pollination time does not interfere in physiological maturity point of tobacco; c) it is not possible to determine the physiological maturity point based on the fruits colour.